Temperature adjusting device, unmanned aerial vehicle hangar and vehicle - GUO BIN; XIAO GUANJIA; ZHONG QUANSI; ZHU LIANGYI; XU SHENGJIE (2025)
The utility model discloses a temperature adjusting device, an unmanned aerial vehicle hangar and a vehicle. The temperature adjusting device comprises a semiconductor thermoelectric device, a first fin device and a second fin device. The first fin device is connected with the first side of the semiconductor thermoelectric device and can conduct heat with the semiconductor thermoelectric device, and the first fin device is used for heat exchange between the semiconductor thermoelectric device and airflow in the unmanned aerial vehicle cabin. The second fin device is connected with the second side of the semiconductor thermoelectric device and can conduct heat with the semiconductor thermoelectric device, and the second fin device is used for heat exchange between the semiconductor thermoelectric device and air flow outside the unmanned aerial vehicle cabin. The temperature of the unmanned aerial vehicle hangar is adjusted through the semiconductor thermoelectric device, the volume occupancy rate is small, the